2016
DOI: 10.1617/s11527-015-0788-y
|View full text |Cite
|
Sign up to set email alerts
|

Ingress of NaCl in concrete with alkali reactive aggregate: effect on silicon solubility

Abstract: Enhanced damage due to the alkali-silica reaction (ASR) in concrete exposed to deicing salt (NaCl) is usually attributed to binding of chloride ions in the hydration products of cement. To balance charge, OH -ions are released into the concrete pore solution which increases alkalinity. However, during NaCl ingress a decrease in the OH -concentration of the concrete pore solution due to potassium leaching would reduce SiO 2 solubility and therefore ASR damage. The present work combines expansion measurements wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…Microstructural changes for concrete specimens were observed in terms of formation of Friedel's salt. The presence of Friedel's salt in the matrix resulting to the NaCl application is in accordance with other researchers findings, [16][17][18][19]. Sutter et al [20] confirmed the formation of Friedel's salt in voids in analyzed concrete specimens exposed to NaCl solution and examined by petrographic methods.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Microstructural changes for concrete specimens were observed in terms of formation of Friedel's salt. The presence of Friedel's salt in the matrix resulting to the NaCl application is in accordance with other researchers findings, [16][17][18][19]. Sutter et al [20] confirmed the formation of Friedel's salt in voids in analyzed concrete specimens exposed to NaCl solution and examined by petrographic methods.…”
Section: Discussionsupporting
confidence: 90%
“…Bérubé et al [16], showed that the high sodium concentration in the near-surface layer of the concrete might not cause severe ASR owing to a decreased OHconcentration in this area. Heising et al [17] stated that the chloride binding on hydrated cement phases and the corresponding release of OHions does not significantly promote ASR. The OHconcentration, and therefore pH, of the concrete pore solution is mainly lowered by potassium leaching, but the OHconcentration is also lowered by the formation of Friedel's salt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent literature shows great interest in the study of ASR. Different subjects related to products and kinetic of the reaction considering the influence of salts [5], powders to promote [6] or inhibit ASR [7], the effects of polymer action [8] were studied. There are also many works that use new NDT methodologies for following ASR [9][10][11][12][13], establish criteria for the characterization and assessment of potentially reactive aggregates [14], or improve accelerated tests, particularly the impact of alkali leaching on scale effects affecting expansion tests [15].…”
mentioning
confidence: 99%